THE OTHER DECADE OF REFORMS IN THE SOCIAL AND LABOR POLICIES. ARGENTINA, 2002-2010 - Danani, Claudia (2013)
The article asserts that in 2003, Argentina began a counter-reform of social policies oriented to neoliberalism during the ‘90s. This process is analyzed stressing political and cultural contents for two specific sectors (labor and retirement policies) and con-textualizing it in the traditional confrontation between peronism and anti-peronism. The conclusion is that the cores of disputes are not on contents of social and labor policies themselves but on global political projects and intentions put by each political sector down to their opositor. A deep ideological fight is the result from this process.